STRATEGIC ENVIRONMENTAL ASSESSMENT FOR PLANNING SUGARCANE EXPANSION: A FRAMEWORK PROPOSAL - GALLARDO,AMARILIS LUCIA CASTELI FIGUEIREDO (2016)
Abstract The Brazilian sugarcane industry has experienced a rapid expansion during the 2000s. The prediction of the sugarcane crop expansion in the coming decades raises controversy about social and environmental impacts, which are partially evaluated in the current energy planning. In order to integrate these discussions to the decision-making, this article aims at presenting a Strategic Environmental Assessment framework to support the sugarcane expansion planning as presented in the national Decennial Energy Plan. The main positive aspects of this framework include: the integration of environmental, social and economic issues providing strategic focus and sustainability to the decision-making; the proposition of sustainability indicators whose data are available for watershed scale; and guidelines for analyzing alternative scenarios established in the energy planning. The authors believe this framework allows integrating sustainability into the decision-making of the sugarcane expansion planning supported by the Strategic Environmental Assessment.